Voices of Identity and Resilience: Exploring Jesmyn Ward’s Selected Narrative Landscapes - Dr. Ritu Kumar and Saloni (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2025)
This research paper discovers the theme of Identity resilience in the literary works of Jasmyn Ward. Jesmyn Ward is an American novelist and professor of English at Tulane University. In Ward’s literary landscape, most themes belong to the race class and marginalization. Her works resonate with postcolonial theory which incorporates the lingering effects of colonial power structure cultural and identity construction in the postcolonial world. Using the lens of Postcolonial Ward’s characters resonate with the theme of identity, many of her characters navigate the social-political legacy of enslavement. Her narratives echo the central tenets of postcolonialism, resistance to domination, reclamation of identity, and search for agency in the operative systems. This research paper examines how word stories intertwine the realities of African American experience with broader post-colonial Frameworks. Authors such as Chimamanda Ngozi Adichie, Salman Rushdie, Jhumpa Lahiri, and Jesmyn Ward, explore similar themes of Identity within post-colonial contexts. By Linking word narrative with essential postcolonial theorists such as Frantz Fanon and Homi Ke Bhabha, this study unravels how her narrative works as a platform for recovering Marginalised voice and negotiating cultural identity.